2013
DOI: 10.5021/ad.2013.25.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Topical Immunotherapy with Diphenylcyclopropenone Is Effective and Preferred in the Treatment of Periungual Warts

Abstract: BackgroundThere exists a treatment challenge with periungual warts. Topical immunotherapy with diphenylcyclopropenone (DPCP) has recently been reported to be an effective treatment for recalcitrant warts, including periungual types.ObjectiveWe aimed to evaluate the effectiveness and preference of topical immunotherapy with DPCP in treating periungual warts.MethodsTwenty-seven patients with periungual warts who were treated with DPCP immunotherapy (2007 through 2010; Dongguk University Ilsan Hospital, Goyang, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
1
23
0
2
Order By: Relevance
“…Periungual warts have proven to be difficult to treat, and recurrences are common . In particular, destructive modalities such as cryotherapy and CO 2 laser ablation are limited when used near periungual regions because they can result in nail deformities . Recent studies have shown that topical immunotherapy with DPCP is a safe and effective treatment for recalcitrant warts, including periungual types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periungual warts have proven to be difficult to treat, and recurrences are common . In particular, destructive modalities such as cryotherapy and CO 2 laser ablation are limited when used near periungual regions because they can result in nail deformities . Recent studies have shown that topical immunotherapy with DPCP is a safe and effective treatment for recalcitrant warts, including periungual types.…”
Section: Discussionmentioning
confidence: 99%
“…In that report, the cure rate was 85% for 27 subjects, which is comparable to other reported treatment modalities for periungual warts: 90% for cryotherapy and 51% for pulsed‐dye laser. Cryotherapy has been reported to have a high cure rate, but its side effects include pain, infection, and nail deformities especially with periungual warts . Immunotherapy has many advantages compared with cryotherapy, including lower complication and recurrence rates and smaller sizes of relapsing warts, as well as the ability to treat multiple lesions simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Periungual wart is a common recalcitrant infectious disease that is challenging to treat . Nail matrix involvement of periungual wart is common, and treatment can cause permanent damage to the nail matrix .…”
Section: Summary Of Cases From Judicial Precedents Associated With Pementioning
confidence: 99%
“…This process is repeated every week until the warts clear [61]. There have been other studies that utilize a sensitization of 2% DPCP instead of a concentration of 0.1%.…”
Section: Immunotherapymentioning
confidence: 99%